Urban associations: class, culture and the enlightened spirit, Derby c.1700-c.1900 - Crane, Michael A (2019)
Essentially an urban biography, this thesis is a social history of Derby’s transformation during the eighteenth and nineteenth centuries. It emphasises the distinctive status of Derby as a county town and examines the synergy of its associative culture, sustained economic growth, thriving knowledge economy and the influence of both elite and plebeian leadership.